2015
DOI: 10.1007/s11517-015-1439-8
|View full text |Cite
|
Sign up to set email alerts
|

Hand–tool–tissue interaction forces in neurosurgery for haptic rendering

Abstract: Abstract:Haptics provides sensory stimuli that represent the interaction with a virtual or telemanipulated object, and it is considered a valuable navigation and manipulation tool during tele-operated surgical procedures. Haptic feedback can be provided to the user via cutaneous information and kinesthetic feedback. Sensory subtraction removes the kinesthetic component of the haptic feedback, having only the cutaneous component provided to the user. Such a technique guarantees a stable haptic feedback loop, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…7 In a tele-operated robotic neurosurgery scenario, haptics provides sensory stimuli that represent the interaction surgeons’ fingers. 8 Aggravi et al 8 work describes the forces exerted on surgical tools by 3 neurosurgeons performing typical actions on a head phantom. The degree of realism of implemented haptic feedback related to the particular task that is being trained will have a key role in the future where the addition of haptics is believed to reduce surgical errors and potentially increase patient safety.…”
Section: The State Of Art On the Introduction Of Technologies For Den...mentioning
confidence: 99%
“…7 In a tele-operated robotic neurosurgery scenario, haptics provides sensory stimuli that represent the interaction surgeons’ fingers. 8 Aggravi et al 8 work describes the forces exerted on surgical tools by 3 neurosurgeons performing typical actions on a head phantom. The degree of realism of implemented haptic feedback related to the particular task that is being trained will have a key role in the future where the addition of haptics is believed to reduce surgical errors and potentially increase patient safety.…”
Section: The State Of Art On the Introduction Of Technologies For Den...mentioning
confidence: 99%
“…Based on the response and recorded data from Figure b with no spacer microstructures, it was found that wider electrode fingers (increased electrode contact surface area) allowed for lower force detection which is ideal and critical for intraventricular neurosurgical operations . The interdigidated electrode pattern with an electrode width of 50 μm showed the least sensibility with a minimum force of 254 ± 79 mN detected.…”
Section: Resultsmentioning
confidence: 98%
“…Intraoperative forces during transnasal endoscopic tumor excision in an in-vivo experiment ranged from 0.1 to 0.5 N, with peak maximal forces up to 2.12 N (Bekeny et al, 2013). Other studies of tool and brain tissue interactions showed a range of forces between 0.5-6 N (Aggravi et al, 2016). A review of 13 studies found mean maximum force output from hand tools in neurosurgery to be 1.48 N. Similarly, the review found that three studies reported a mean maximum force output from retraction tasks to be 2.5 N (Golahmadi et al, 2021).…”
Section: Clinical Requirementsmentioning
confidence: 88%